THE RELATIONSHIP BETWEEN FAMILY SUPPORT AND INTERNET DEPENDENCE IN ADOLESCENTS AT PATRIOT VOCATIONAL SCHOOL, MANCAR, PETERONGAN, JOMBANG - Sapulete, Evanly Y.; Rustanti, Elly; Setiawan, Roni (Literasi Kesehatan Husada: Jurnal Informasi Ilmu Kesehatan, 2023)
Background: Family support has an important role in developing adolescents' social skills by providing pleasant interactions. Adolescents who feel they have tenuous ties to family support may have lower social skills and less appropriate coping strategies. One way for adolescents to fulfill these needs is through the internet which can facilitate them to establish interpersonal relationships with other people. Internet addiction can cause an inability to control the desire to use the internet, experiencing problems such as depression, feeling disturbed, and not being able to stand it when you stop using the internet. Objective: The aim of this research was to determine the relationship between family support and internet dependence among adolescents at Patriot Vocational School, Mancar, Peterongan, Jombang. Method: The design of this research is analytic-cross sectional. The population in this study were all adolescents at Patriot Vocational School, Mancar, Peterongan, Jombang, mostly using purposive sampling techniques with a sample size of 36 respondents. Data collection used a questionnaire and data analysis used Spearman Rho. Results: The research results showed that the majority of respondents had good family support, 23 respondents (63.9%) and the majority of respondents had moderate internet dependence, 20 respondents (55.6%). The results of the Spearman rho data analysis obtained p < α= 0.00 and the error level or α is 0.05, so p < α (0.00 < 0.05) so that H1 is accepted, there is a relationship between family support and internet dependence in teenagers. . Conclusion: Based on the research results obtained, it can be concluded that there is a relationship between family support and internet dependence, so with this research it is hoped that teenagers can obtain good information in preventing internet dependence.